A cross-national study of evolutionary origins of gender shopping styles: she gatherer, he hunter? - Dennis, Charles; Brakus, J. Joško; García Ferrer, Gemma; McIntyre, Charles; Alamanos, Eleftherios; King, Tamira (SAGE, 2018)
By investigating gendered shopping styles across countries, the authors explore whether the differences between male and female shopping styles are greater than the differences in shopping styles exhibited by consumers across countries. With a conceptual model, this study tests an extant convergence hypothesis that predicts that men and women should grow more similar in their shopping styles as traditional gender-based divisions in wage and domestic labor disappear. The results of a survey of shopping behavior across 11 countries indicate though that men and women are evolutionarily predisposed to different shopping styles. These differences in shopping styles also are greater in countries with higher levels of gender equality. Empathizing, or the ability to tune in to others’ thoughts and feelings, mediates shopping styles more for women; systemizing, or the degree to which a person possesses spatial skills, mediates shopping styles more for men. These results suggest that gender-based retail segmentation is more strategically relevant than country-based segmentation. The authors discuss the implications of their findings for international marketing theory and practice.
Keywords: shopping styles; gender; evolutionary psychology; international market segmentation